The effect of follicle-stimulating hormone administration on the day of human chorionic gonadotropin trigger on assisted reproductive technique outcomes in patients undergoing In vitro fertilization-embryo transfer: A retrospective cohort study - Chithira Pulimoottil Vignarajan; Neeta Singh; Perumal Vanamail (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim is to study the effect of follicle-stimulating hormone (FSH) administration on the day of human chorionic gonadotropin (hCG) trigger on the assisted reproductive technique (ART) outcomes in in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles. Settings and Design: Retrospective cohort study was conducted in the ART center of our hospital. Materials and Methods: Two hundred and ninety IVF/ICSI cycles performed between September 2012 and August 2017 were included in the study. Patients who received 375 IU of FSH on the day of hCG trigger (149 cycles) were compared with those who did not receive FSH on the day of trigger (141 cycles). Statistical Analysis Used: Chi-square test and Student's t-test were used. Results: The FSH co-administered group had a significantly higher number of oocytes retrieved, mature oocytes, and fertilization rate compared to those who did not receive FSH on the day of trigger (p < 0.001). The total number of embryos, the number of grade 1 embryos and the number of embryos available for cryopreservation were also significantly higher in the FSH administered group (p < 0.001). Implantation rate, clinical pregnancy rate, and live birth rate were not significantly different between the two groups. Conclusions: This study has shown that FSH administration on the day of the trigger may be considered in IVF cycles receiving hCG trigger to improve the oocyte recovery and maturity if the patient is not at increased risk of ovarian hyperstimulation and serum estradiol on the day of the trigger is <4500 pg/ml. However, there is only an increase in the total number of oocytes retrieved and the number of mature oocytes but no significant change in the implantation, clinical pregnancy, and live birth rates.